What does it take to do successful adaptive management? A case study highlighting Coastal Grassy Woodland restoration at Yanakie Isthmus. (May 2018) - Morgan, John; Wright, John; Whelan, Jim; Clarke, Michael; Coulson, Graeme; Lunt, Ian; Stoner, John; Varcoe, Tony; Shannon, James
Abstract : The case study of the Yanakie Isthmus Coastal Grassy Woodland Restoration Program, Victoria, Australia, illustrates the steps necessary to deliver a complex, long‐term adaptive management project involving a range of stakeholders at a landscape scale. Perspectives of the land manager, scientist and volunteer help to convey successes and lessons learned.